PENGARUH HUBUNGAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIBEL MODERATING - Ambarini, Ernawati & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
ABSTRACT The aims of this research is to examine the effect of: (1) The working relationship to performance, (2) work environment on performance, (4) Work motivation moderate the influence of the working relationship and work environment on staff performance Karanganyar District Personnel Agency. Employee population of the District Personnel Agency Karanganyar numbered 54 people. Conclusion The results of the study: (1) The hypothesis that says: "there is significant influence working relationships to employee performance Karanganyar District Personnel Agency" unsubstantiated claims, (2) The hypothesis that says: "There is a significant influence on the performance of employees of the Work Environment Agency Regional Personnel Karanganyar District "does not prove its truth, (3) The hypothesis that says: " The variable job motivation moderate the influence of the working relationship and work environment on staff performance Karanganyar District Personnel Agency ", not attested. Keywords: Employment, work environment, employee motivation and performance officer.